Pelatihan Budidaya Ikan Dan Sayuran Dengan Media Akuaponik Di Kecamatan Sajad Kabupaten Sambas - Sangkala, Sangkala; Agam, Beryaldi; Heriyansah, Heriyansah (Pakis Journal Institute, 2025)
Aquaponic system fish farming in Indonesia is a relatively new technology and is not widely known by fish farmers. Aquaponics system fish farming technology is a combination of fish farming and vegetable crop farming in one unified system. The purpose of this devotion is 1). Providing knowledge, understanding, and skills of the community in making aquaponic cultivation of vegetable and tilapia plants; 2). Provide training on mechanisms and procedures for making tilapia farming businesses aquaponically; 3). Knowing the analysis of tilapia farming business in aquaponics. The implementation of community service (PKM) was carried out on September 5, 2022 and September 11, 2022 at the